Pengaruh Pengelolaan Dana Desa Dan Transparansi Dana Desa Terhadap Kesejahteraan Masyarakat - Asrul, Asrul (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2024)
This study aims to determine the effect of Village Fund Management and Village Fund Transparency on Community Welfare (Study in Nagari Sikucua Barat District V Koto Kampung Dalam Padang Pariaman Regency. This research is a type of quantitative research with an explanatory approach using primary data. Primary data obtained from Questionnaires were distributed to 90 respondents, and this data was tabulated using the excel program and processed with the help of SPSS software version 18. The results showed that village funds had an influence on community welfare with a t-count value of 14.735, which means more than t-table. is 1,991 (14,735 > 1,991) with a significance level of 0.000 which means less than 0.05 (0.000 < 0.05). The transparency system has a positive and significant effect on people's welfare with a t-count value of 1.909 > 1.991 with a significance level of 0.060 which means rti less than 0.05 (0.060 < 0.05). The Village Fund, and the transparency system simultaneously affect the welfare of the community. This is indicated by the calculated F value of 180.859 > 3.09 with a significant 0.000 which is smaller than 0.05. This is evidenced that the existence of good village fund management and based on good transparency can create a good level of community welfare.